Are Fallacies Frequent? - Dufour, Michel (Informal Logic)

(untitled) (Informal Logic, 2023)
This paper provides methodological tools and considers the reasons why it is difficult to address the controversial question, “Are fallacies frequent?” After preliminary remarks on the need to clarify the meaning of both ‘fallacy’ and ‘frequency,’ this paper shows that the emphasis on whether fallacies occur frequently is recent and bound to contemporary definitions that make it a necessary condition. Then, it discusses three different, debated empirical approaches that are intended to support the claim that fallacies are frequent. All of them raise doubts or objections or are even controversial from a methodological point of view. Ultimately, more empirical research is needed to answer this question.